2005
DOI: 10.1128/mcb.25.17.7557-7568.2005
|View full text |Cite
|
Sign up to set email alerts
|

The Transmembrane Adapter Protein SIT Regulates Thymic Development and Peripheral T-Cell Functions

Abstract: SIT is a transmembrane adapter protein that modulates signals emanating from the T-cell receptor (TCR

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
58
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(66 citation statements)
references
References 55 publications
7
58
1
Order By: Relevance
“…CD8 ϩ T cells were either left untreated or stimulated with CD3/CD8 mAbs or OT-I-streptamers, lysed as described in (13) and protein concentration was determined using the Roti-Nanoquant reagent (Roth) according to manufacturer's instruction. The samples were analyzed by Western blotting.…”
Section: Western Blotting and Immunoprecipitationmentioning
confidence: 99%
“…CD8 ϩ T cells were either left untreated or stimulated with CD3/CD8 mAbs or OT-I-streptamers, lysed as described in (13) and protein concentration was determined using the Roti-Nanoquant reagent (Roth) according to manufacturer's instruction. The samples were analyzed by Western blotting.…”
Section: Western Blotting and Immunoprecipitationmentioning
confidence: 99%
“…Moreover, we have shown that SIT Ϫ/Ϫ mice displayed an enhanced positive selection in the thymus, hyperactivated peripheral T cells, and an increased homeostatic proliferation [7][8][9]. Conversely, mice lacking TRIM [10], PAG [11,12], and LIME [13] have no significant alteration of the immune system.…”
Section: Introductionmentioning
confidence: 89%
“…Recently, it has been shown that SIT and LAX are negative regulators of lymphocyte activation [5,7,9]. However, as SIT Ϫ/Ϫ and LAX Ϫ/Ϫ mice display only mild alterations in immune functions, we investigated whether the loss of SIT and LAX would result in a more severe phenotype than the single KOs.…”
Section: Accumulation Of Activated Cd4 ؉ T Cells In Dko Micementioning
confidence: 99%
See 2 more Smart Citations